2002
DOI: 10.1046/j.1365-2524.2002.00365.x
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in access to healthcare faced by women who are deaf

Abstract: The Cheshire Deaf Women's Health Project undertook a research study to assess the access to healthcare of women who are deaf in Cheshire, UK. Group discussions took place with 13 women who were hard of hearing and 14 women who were Deaf Sign Language users. Questionnaires were distributed to a stratified random sample of 103 women taken from the social services register, 38 of which were returned. In order to reach more women whose first language was British Sign Language, 129 questionnaires were distributed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
1
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 13 publications
4
48
1
8
Order By: Relevance
“…Outro estudo com mulheres de diferentes tipos de deficiência auditiva confirma esses achados. Também confirma o fato de as pacientes sentirem-se envergonhadas, com medo de consultas e procedimentos em saúde, desconhecendo termos médicos e seus próprios corpos 3 . O mesmo artigo nota ainda que a maioria dos serviços de saúde, inclusive clínicas especializadas em audiologia, trabalha com um sistema de chamar em voz alta os nomes dos pacientes, o que limita o acesso destes e gera ansiedades e preocupações 3,6,8 .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Outro estudo com mulheres de diferentes tipos de deficiência auditiva confirma esses achados. Também confirma o fato de as pacientes sentirem-se envergonhadas, com medo de consultas e procedimentos em saúde, desconhecendo termos médicos e seus próprios corpos 3 . O mesmo artigo nota ainda que a maioria dos serviços de saúde, inclusive clínicas especializadas em audiologia, trabalha com um sistema de chamar em voz alta os nomes dos pacientes, o que limita o acesso destes e gera ansiedades e preocupações 3,6,8 .…”
Section: Discussionunclassified
“…No Reino Unido, o envelhecimento da população acarretará um aumento aproximado de 20% de deficientes auditivos nos próximos vinte anos. A perda auditiva é freqüentemente subdiagnosticada, especialmente nos idosos 3 .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Recent community-based participatory research has identified some glaring health inequalities in the deaf community, notably obesity, partner violence, and suicide (Barnett et al 2012), while other studies have demonstrated inconsistent knowledge of common health issues such as cardiovascular health related to difficulties with communication during health education (McKee et al 2011). Fewer than one in ten deaf women report fully understanding what the doctor tells them when visiting the doctor's office alone (Ubido 2002).…”
Section: Implications Of Early Hearing Loss For Health Development Ovmentioning
confidence: 99%
“…1 Deaf and hard of hearing (D&HH) persons, as a group, have lower socioeconomic status, 2 altered health-care utilization patterns, 3,4 and significant communication difficulties with health-care workers. 5,6 Some D&HH persons belong to the Deaf community, a wellrecognized ethnic minority 4,7 with its own language (American Sign Language, ASL, in the US), culture and beliefs. [8][9][10][11] ASL is a complete language with unique idioms, syntax, and grammar.…”
Section: Introductionmentioning
confidence: 99%